Apprendre à enseigner des années 1970 aux années 1990 : d’une forme de domination scolaire à l’autre ? - Stéphane Vaquero (Genre & Histoire)
From the 1970s to the 1990s, training to become a secondary school teacher deeply changed. Criticized for their "lack of pedagogy" and for the cultural arbitrariness of the knowledge they passed on, teachers trained during the 1970s did nevertheless learn how to teach during their year of training. The biographical portraits of two teachers of history and geography who were taught the job during the 1970s, as well as a work on their student archives, show this learning process. During the 1990s, the "professionalization" of teachers challenged these ways of teaching, considered ineffective and a cause of social inequalities. Observing the daily work of these two generations of teachers in a high school shows a more complex reality. The evolution of the ways of becoming a teacher, of gender relations and of cultural practices have altered, more than lessened, the socially unequal character of academic learning.